Development of 2-colour and 3D SMLM data analysis methods for fibrous spatial point patterns. (5th November 2018) - Peters, R; Griffié, J; Williamson, D J; Aaron, J; Khuon, S; Owen, D M
Abstract: Single molecule localisation microscopy (SMLM), experimentally achieved over a decade ago, has become a routinely used analytical tool across the life sciences. A prevalent theme in the SMLM field is the need for quantitative analytical methods, owing to the point pattern nature of SMLM data. Whilst some forms of post processing analytics, for example cluster analysis, have been widely studied, others such as fibre analysis remain in their infancy. Here, we present two methods based on variants of Ripley's K-function for the analysis of fibrous structures in 3D and for dual colour data with one fibrous and one clustered molecular species. We demonstrate the methods on both simulated and experimental data of the actin cytoskeleton at the T cell immunological synapse.